Imperfect collusion on surveilled markets with free entry - Ludwig von Auer; Tu Anh Pham (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2023)
Surveys of cartel proceedings reveal that illegal cartels usually (1) attempt to minimize the risk of detection, (2) achieve merely imperfect levels of collusion, (3) compete against some fringe firms, and (4) adjust to market entries and exits. By contrast, existing oligopoly models of collusive behavior consider only some of the four listed stylized facts and, thus, run the risk of missing important interdependencies between them. Therefore, the present paper develops a general quantity leadership model that simultaneously accommodates all four stylized facts. Within this model, an imperfectly colluding group of firms competes against independent fringe rivals. The market is surveilled by an antitrust authority that has three different policy instruments at its disposal: Ensuring free market access, obstructing collusion, and discouraging collusion through law enforcement. The results of the model indicate that the latter two instruments are rather ineffective.
Keywords: L0; L1; 330; antitrust; fringe; oligopoly; stability; sustainability